Aggregation Model to Determine Criteria Weights for Integrated Primary Health Care Information System (IPCIS) Implementation - Kusumadewi, Sri; Kurniawan, Rahadian; Wahyuni, Elyza Gustri; Arifin, Aridhanyati; Rosita, Linda; Mutmainna, Mutmainna (Jurnal Teknik Informatika (Jutif), 2026)
Implementation of the Integrated Primary Health Care Information System (IPCIS) in integrated community health posts (posyandu) is influenced by various factors, including technical aspects, human resources, policies, and data governance. Given the diverse field conditions, the impact of each factor can vary, so it is important to understand the relative importance of each criterion. This study aims to determine the weight of the criteria that influence the implementation of IPCIS in posyandu. Ten people answered the questions correctly (out of 22 respondents), including cadres, sub-district staff, and health workers from Tirtorahayu Village. Respondent preferences were collected using three approaches: rank-based aggregation (Borda, Condorcet, Copeland), score-based aggregation (average), and voting-based aggregation (plurality and majority) to obtain the criteria weights (w) and a comparative analysis between the approaches. The findings demonstrate that the IPCIS criteria for security and protection of personal data were consistently given the highest weights. In the ranking-based aggregation approaches (w_Borda=0.11, w_Condorcet=0.20, w_Copeland=0.19). In score-based aggregation approaches (w=0.11). In voting-based aggregation approaches (w=0.15). It is indicating a strong group consensus regarding the importance of these aspects in IPCIS implementation. The combination of ranking-based and score-based aggregation resulted in stable IPCIS implementation criterion weights that reflected group consensus, with voting-based aggregation acting as validation. The practical implication is that the obtained weighted criteria can be used as a basis for determining program priorities and resource allocation when implementing IPCIS.